What Are Isolation Valves, and How Do They Work?. Issue 11 (4th November 2020) - White, Robb
Abstract : Most valves installed in a water system are intended to start and stop flow. Designed to be either fully open or fully closed under normal conditions, these valves are commonly referred to as isolation valves.